The distribution and changes of Phytophthora infestans population in Latvia - Bebre, Gunta; Skrabule, Ilze; Osa, Marija (Plant Breeding and Seed Science, 2004)
Potato breeders and phytopathologists have been conducting the studies on Phytophthorainfestans (Mont.) de Bary at the Priekuli Plant Breeding Station since 1962. The varietal resistanceis very important in potato breeding programme. The trials in collaboration with the Institute ofPhytopathology of Soviet Union (Russia) were done in 1974-1990. The investigations were focusedon races of P. infestans. The changes of races were assessed using a trap method, according to theinvestigation programme, like in each of the republics of the Soviet Union.At the beginning of investigations (1960s and 1970s) races 1, 4 and 1.4 of P. infestans were thepredominant ones in Latvia, but in the 1980s complex races 4.10.11, 1.4.7.8.10.11, 1.3.4.7.8.10.11and 1.2.3.4.7.8.10.11 were more widely distributed.Different foreign varieties, mostly from the Netherlands, were introduced in Latvia in the 1970s.This resulted in a very rapid differentiation of late blight races. The enhanced aggressiveness of P.infestans isolates was due to an increasing number of races in population. The earlier appearance ofinfection in potato fields was recorded. The presence of a mating type A2 was stated in Latviansamples in 1987. Because all tested races had been recognized in a population, and the conception ofresistance breeding had been modified, the trials were stopped in 1990. The resistance based onspecific resistance genes was the main direction in the 1960s and 1970s. From the 1980s, impor-tance of the field resistance has greatly increased and this type of resistance is the most significantin the current breeding programme. The trials in organic field proved the acceptable level of fieldresistance to P. infestans of three medium late varieties: Sigunda (previous name Undine), Beteand Zile. These varieties have been bred at the Priekuli Plant Breeding Station and included intothe Latvian Plant Varieties Catalogue.